The grand design - Hawking, S. W., (Stephen W.); Mlodinow, Leonard, 1954- (New York : Bantam Books, 2010)
Presents a new study of the cosmos that explains the latest theories on why the universe and life exist and why they work the way they do, through the concept of the multiverse, or "m-theory," that attempts to construct a grand unified design.
Originally published: London : Bantam, 2009.
Includes index.
Keywords: Cosmology; Cosmology -- Research; Physics; Physics -- Research; Cosmology; Cosmology -- Research; Physics; Physics -- Research